2019
DOI: 10.1177/0963689719835181
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum(Wolfberry) Increases Retinal Ganglion Cell Survival and Affects both Microglia/Macrophage Polarization and Autophagy after Rat Partial Optic Nerve Transection

Abstract: The rat partial optic nerve transection (PONT) model has been used for studying secondary degeneration of retinal ganglion cells (RGCs) in recent years. In this study, we carried out PONT of the temporal side of rat optic nerves, whereas PONT was carried out of the superior side in the previous publication. We found that this surgery is better and easier than the previous method and can produce a repeatable and reliable model. We detected significant changes in the polarization of microglia/ macrophages and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…Polysaccharides are the most important biologically active compounds in L. chinense; they have extensive biological functions [43,44]. As a key component of L. chinense, polysaccharides are important for maintaining healthy eyes [45,46], preventing protecting cardiac function [47,48] and preventing heart failure and diabetes [49,50]. In our study, the polysaccharide content of L. chinense was consistent with that of L. barbarum, indicating that L. chinense also have potential value as a functional food [39,43].…”
Section: Rutin Contentsupporting
confidence: 67%
“…Polysaccharides are the most important biologically active compounds in L. chinense; they have extensive biological functions [43,44]. As a key component of L. chinense, polysaccharides are important for maintaining healthy eyes [45,46], preventing protecting cardiac function [47,48] and preventing heart failure and diabetes [49,50]. In our study, the polysaccharide content of L. chinense was consistent with that of L. barbarum, indicating that L. chinense also have potential value as a functional food [39,43].…”
Section: Rutin Contentsupporting
confidence: 67%
“…Under this condition, cultures containing low-glucose medium were first placed in a hypoxia chamber (95% N 2 + 5% CO 2 ) for 1 h and then closed for 18 h ( Kanazawa et al, 2017 ). In addition, several drugs, such as minocycline ( Ahmed et al, 2017 ) and Lycium barbarum ( Li et al, 2019b ), were reported to modulate microglial polarization from the M1 to M2 phenotype in some in-vivo models. However, further studies are needed to determine whether they can be used to induce M2 polarization of microglia in vitro .…”
Section: Future Directionsmentioning
confidence: 99%
“…In rats that had undergone partial optic nerve transection (PONT) feeding with LBP, for 7 days before the insult, there was delayed secondary RGC degeneration and improved retinal function by inhibiting oxidative stress, increasing the JNK/c-jun pathway and modulating the activation of microglia/macrophages in the retina [ 292 , 293 ]. More recently, the neuroprotection afforded by LBP in the PONT model has been associated with the increase of macrophage M2 polarization and the reduction of the autophagy marker LC3II [ 294 ].…”
Section: Lycium Barbarummentioning
confidence: 99%